Where are We at and Where are We heading to? - Sergio Eduardo de Paiva Gonçalves (Brazilian Dental Science)
The Scientific world has undergone a significant change. Countries up to now known as consumers of science produced by major world centers, have become producers of knowledge. The presence in Congresses, Symposia and International Scientific Meetings highlights this change. Recent data presented at SBPqO (Brazilian division of the IADR) showed that Brazil now occupies a highlighted position on the number of submissions to high impact Dental journals (2nd place). However, the scientific community does not share these data in order to enable better distribution of information generated by foreign countries. In other words, publication of results still suffers the negative direct influence of a protectionist and shadowy policy. This paradigm change depends fundamentally on researchers themselves, who should seek other sources for their publications, increasing the impact of journals that have the commitment to serious, ethical and unrestricted access science. This attitude would have the beneficial reflex to increase the range of possibilities for publication, thereby increasing the exchange of information among research  groups. The future of global science is directly related to the attitudes of today’s professionals. Recognize that other possibilities for your publication exist; the visibility of your results depends on the expansion of qualified new journals. Cordial greetings and entertain yourself with a new issue of the Brazilian Dental Science (BDS).